Cultural Trauma and Collective Identity - Alexander, Jeffrey C. (Book collections on Project MUSE., 2004)
In this collaboratively authored work, five distinguished sociologists develop an ambitious theoretical model of "cultural trauma"--And on this basis build a new understanding of how social groups interact with emotion to create new and binding understandings of social responsibility. Looking at the "meaning making process" as an open-ended social dialogue in which strikingly different social narratives vie for influence, they outline a strongly constructivist approach to trauma and apply this theoretical model in a series of extensive case studies, including the Nazi Holocaust, slavery in the